Photon-Enhanced AI Platforms for Multimodal Therapeutics - Barack Ndenga (Publisher, 2025)
This study presents a next-generation computational pharmacology architecture: Photon-Enhanced AI Platforms for Multimodal Therapeutics (PEAI-MT). Unlike conventional therapeutic design frameworks, which typically rely on linear screening and fixed chemical parameters, PEAI-MT leverages multi-spectral photonic control integrated with adaptive artificial intelligence algorithms to enable real-time co-design of molecular, photonic, and nanotechnological therapeutic strategies. The platform operates by dynamically modulating photon wavelengths and intensities to precisely influence molecular interactions, binding dynamics, and energy landscapes. This allows the creation of hybrid treatment modalities—for example, combining chemotherapy with phototherapy and nanotechnology—designed specifically for each biological target. By treating light not as a passive accelerator but as an active design variable, PEAI-MT achieves significantly higher molecular precision, reduces computational costs, and accelerates therapeutic development cycles. Early computational evaluations indicate that spectral adaptation improves energy mapping fidelity and enhances therapeutic specificity. This paradigm shift establishes the foundation for autonomous, intelligent, and light-driven therapeutic engineering, paving the way for next-generation treatments that are personalized, adaptive, and multimodal.
This work presents the Photon-Enhanced AI Platforms for Multimodal Therapeutics (PEAI-MT), an innovative computational framework that integrates photonic computation, artificial intelligence, and molecular modeling to design hybrid therapies in real time. By leveraging multi-wavelength spectral control, adaptive AI optimization, and molecular reconstruction, the platform enables the co-creation of chemical, photonic, and nanotechnological therapies with unprecedented precision, speed, and efficacy. The PEAI-MT system represents a paradigm shift from traditional single-modality drug development to intelligent, adaptive, and multimodal therapeutic design. Applications include oncology, virology, neurodegenerative diseases, and antimicrobial therapy, demonstrating the potential for rapid, personalized, and high-throughput drug discovery. This 23ᵉ article builds upon the previously developed Photonically-Assisted AI Drug Design Pipeline (PAI-DDP) framework (19ᵉ–21ᵉ articles), extending its capabilities to fully integrated multimodal therapeutic engineering. Original contribution: The platform transforms light into an active design parameter, allowing AI-guided spectral modulation to optimize molecular interactions, enabling real-time creation of next-generation therapies.